2014
DOI: 10.1590/s1677-5538.ibju.2014.01.02
|View full text |Cite
|
Sign up to set email alerts
|

A review of continuous vs intermittent androgen deprivation therapy: Redefining the gold standard in the treatment of advanced prostate cancer. Myths, facts and new data on a perpetual dispute

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Objectives: To review the literature and present new data of continuous androgen deprivation therapy (ADT) vs intermittent androgen deprivation (IAD) as therapies for prostate cancer in terms of survival and quality of life and clarify practical issues in the use of IAD. Materials and Methods:We conducted a systematic search on Medline and Embase databases using "prostatic neoplasm" and "intermittent androgen depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 46 publications
(53 reference statements)
0
26
0
Order By: Relevance
“…(≈ 150 hours) [14] enables an oscillation period of approximately a week ( Figure 5B). This timescale is comparable with various hormone-deprivation treatments applied in the clinic [35,36] and motivated investigating the effect of various therapies. As a first step, we considered a constant inhibitory signal acting on the Androgen Receptor (AR), to simulate the effect of continuous Androgen Depri-vation Therapy (ADT) -the standard care of therapy for over 75 years for locally advanced and/or metastatic PCa [35].…”
Section: Implications Of Switching Between Clk2-page4 and Hipk1-page4mentioning
confidence: 88%
“…(≈ 150 hours) [14] enables an oscillation period of approximately a week ( Figure 5B). This timescale is comparable with various hormone-deprivation treatments applied in the clinic [35,36] and motivated investigating the effect of various therapies. As a first step, we considered a constant inhibitory signal acting on the Androgen Receptor (AR), to simulate the effect of continuous Androgen Depri-vation Therapy (ADT) -the standard care of therapy for over 75 years for locally advanced and/or metastatic PCa [35].…”
Section: Implications Of Switching Between Clk2-page4 and Hipk1-page4mentioning
confidence: 88%
“…Multiple clinical trials have demonstrated that IADT may reduce the adverse effects associated with continuous ADT without any clear difference in survival 26 . Long term efficacy remains to be determined and methods for optimization of IADT will be a critical step in establishing it as a viable treatment option, especially in patients with advanced metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recent reviews comparing efficacy, side effects, time to castration resistance, overall and cancer-specific survival between intermittent and continuous ADT have been summarised; however, the evidence regarding the tradeoffs between the benefits and risks of intermittent ADT remains inconclusive. [17][18][19][20][21][22][23] Generally the consensus is that overall survival is equivalent between intermittent and continuous ADT in most settings. However, concerns remain with high-risk disease, as one of the larger trials did not meet criteria for non-inferiority of an intermittent regimen in men with metastatic cancer.…”
Section: How Might This Impact On Clinical Practice?mentioning
confidence: 99%